Emulsifying properties of bile salt and its competitive adsorption with other emulsifiers : a thesis presented in partial fulfillment of the requirements for the degree of Master of Technology in Food Technology at Massey University, Albany, New Zealand - He, Jing (Massey University, 2021)
Emulsion is a common form of food products that additionally offers food functionalization, such as encapsulation and delivery of vitamins, etc. Emulsion formation and stabilization as well as the rate of digestion has been extensively studied. During the digestion, the presence of emulsifiers in the emulsion may compete for the oil-aqueous interface with bile salts (BS), a bio-surfactant synthesized in a body. Since bile salts play an important role in fat digestion, the aim of this study is to explore the interaction of bile salts with commercially available emulsifiers at the oil-water interface. In order to examine the capability of bile salts to adsorb at the interface, the droplet size, zeta-potential and creaming index of emulsions stabilized by bile salts were investigated and compared with those of WPI and Tween stabilized emulsions. Subsequently, the competitive adsorption of bile salts and its ability to displace WPI and Tween on the oil-water interface was studied in the similar manner, i.e., through investigation of the emulsion properties as well as interfacial tension. The results suggested that BS had better emulsifying ability than WPI and Tween, indicating that it had a better ability to adsorb onto oil-water interfaces. The results for competitive adsorption suggested that BS was able to displace almost entirely the Tween 80 from the oil-water interface but it might not displace the WPI completely. These results complement available information on the fat digestion mechanism and processes.
The Following Figures were removed for copyright reasons: 1 (=Macierzanka et al., 2019 Fig 1), 2.1 (= Maldonado-Valderrama et al., 2011 Fig 1b), 2.2 (=Euston et al., 2013 Fig 1), 2.7, 2.8, 2.9, 2.10, 2.11, 2.12 (=McClements 2007 Figs 2, 6, 8, 1, 3, 4), and 2.15 & 2.16 (= Berry et al., 2015 Figs 1 & 2). Figures 2.4, 2.5, 2.6, 2.14 (=McClements, 2015) remain for clarity's sake.
Keywords: 300607 Food technology